2008
DOI: 10.1073/pnas.0801205105
|View full text |Cite
|
Sign up to set email alerts
|

HilD-mediated transcriptional cross-talk between SPI-1 and SPI-2

Abstract: The acquisition of new genetic traits by horizontal gene transfer and their incorporation into preexisting regulatory networks have been essential events in the evolution of bacterial pathogens. An example of successful assimilation of virulence traits is Salmonella enterica, which acquired, at distinct evolutionary times, Salmonella pathogenicity island 1 (SPI-1), required for efficient invasion of the intestinal epithelium and intestinal disease, and SPI-2, essential for Salmonella replication and survival w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
230
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(246 citation statements)
references
References 55 publications
16
230
0
Order By: Relevance
“…Regulation of the taiA invasin by PhoP may seem to contradict its well-accepted function as a regulator of virulence genes involved in intracellular survival, such as the SPI-2 T3SS. However, using LB broth, a condition not usually recognized to support expression of genes involved in intracellular survival, it has been shown that pag genes, controlled by PhoP, and some SPI-2 effectors are expressed (Belden & Miller, 1994;Bustamante et al, 2008). Moreover, it was recently shown that two genes encoded on SPI-1 (orgBC) are activated by PhoP during growth in LB NaCl, a condition known to induce SPI-1 genes (Aguirre et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of the taiA invasin by PhoP may seem to contradict its well-accepted function as a regulator of virulence genes involved in intracellular survival, such as the SPI-2 T3SS. However, using LB broth, a condition not usually recognized to support expression of genes involved in intracellular survival, it has been shown that pag genes, controlled by PhoP, and some SPI-2 effectors are expressed (Belden & Miller, 1994;Bustamante et al, 2008). Moreover, it was recently shown that two genes encoded on SPI-1 (orgBC) are activated by PhoP during growth in LB NaCl, a condition known to induce SPI-1 genes (Aguirre et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…1.2). For example, HilD, the master activator of SPI-1 genes has been shown to regulate transcription of the ssrA/B operon, encoding the key regulator of SPI-2 (Bustamante et al, 2008;Martinez et al, 2014).…”
Section: Salmonella As a Model Organism For Host-pathogen Interactionmentioning
confidence: 99%
“…Different studies have shown that low oxygen, high osmolarity, the exponential phase of growth and slightly alkaline pH induce hilA expression and consequently the invasion genes (Bajaj et al, 1996;Jones & Falkow, 1994;Chubiz et al, 2010) Other recent studies have shown that, when Salmonella cells are grown in aerated Luria-Bertani (LB) medium at 37 uC, hilA induction occurs at the onset of the stationary phase (Song et al, 2004;Mangan et al, 2006;Bustamante et al, 2008). These culture conditions have been used to further analyse the effects of modulators such as ppGpp (Song et al, 2004) and integration host factor (IHF) (Mangan et al, 2006), and the regulatory cross-talk between SPI1 and SPI2 (Bustamante et al, 2008). Most likely, low oxygen/exponential growth phase and aeration/ early stationary phase mimic different environmental inputs that Salmonella cells detect when growing in natural environments, and lead to hilA induction.…”
Section: Introductionmentioning
confidence: 99%